Effectiveness of Wordwall Learning Media in Enhancing Students’ Ability to Write Formal Letters in Indonesian Language Learning - Dhea Nazaliya; Muhammad Aridan (JPI: Jurnal Pustaka Indonesia, 2024)
Classical Arabic poetry plays an essential role in preserving cultural identity and religious values, with Hassan bin Tsabit recognized as one of the foremost poets of the early Islamic period whose works encapsulate spiritual devotion and socio-historical experience. This study aimed to analyze the poem Al-Fida’ by Hassan bin Tsabit through the lens of Wilhelm Dilthey’s hermeneutics, focusing on the triadic concepts of Erlebnis (lived experience), Ausdruck (expression), and Verstehen (understanding). Employing a qualitative descriptive design, data were collected through library research using the critical edition of Hassan’s Diwan alongside supporting secondary sources, and analyzed by systematically classifying figurative language, symbolic expressions, and contextual references. The results show that the poem reflects the poet’s personal piety and collective consciousness, articulated through symbolic imagery and emotive language that merge individual faith with communal identity. The discussion indicates that Dilthey’s hermeneutic framework provides a structured means of interpreting classical Arabic poetry not merely as aesthetic expression but also as cultural testimony embedded in historical and religious contexts. The implication of this study is that hermeneutic analysis enriches literary scholarship by offering both theoretical insights into interpretive methodologies and practical contributions for integrating classical poetry into modern education and cultural studies.